2021
DOI: 10.3389/fonc.2021.654940
|View full text |Cite
|
Sign up to set email alerts
|

Salubrinal Exposes Anticancer Properties in Inflammatory Breast Cancer Cells by Manipulating the Endoplasmic Reticulum Stress Pathway

Abstract: The endoplasmic reticulum (ER) regulates protein folding, post-translational modifications, lipid synthesis, and calcium signaling to attenuate the accumulation of misfolded proteins causing ER stress and maintains cellular homeostasis. The tumor microenvironment is rich in soluble cytokines, chemokines, growth, and angiogenic factors and can drive the ER’s abnormal functioning in healthy cells. Cancer cells adapt well to the tumor microenvironment induced ER stress. We identified that the inflammatory breast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 70 publications
(103 reference statements)
0
8
0
Order By: Relevance
“…Lane et al reported that OPG inhibited the TRAIL-mediated apoptosis of ovarian cancer cells in an α v β 3 and α v β 5 integrin-dependent manner [ 46 ]. In inflammatory breast cancer, OPG interacted with glucose-regulated protein/binding immunoglobulin protein (GRP78/BiP), the endoplasmic reticulum (ER) chaperone and master regulator of the unfolded protein response, to promote cell apoptosis and prolong the survival of inflammatory breast cancer cells [ 47 ]. By forming complexes with the lipid raft core protein Cav-1 and EGFR, RANK promoted gastric cancer cell migration, and this effect was mitigated by OPG [ 48 ].…”
Section: Molecular Structure and Expression Of Opgmentioning
confidence: 99%
“…Lane et al reported that OPG inhibited the TRAIL-mediated apoptosis of ovarian cancer cells in an α v β 3 and α v β 5 integrin-dependent manner [ 46 ]. In inflammatory breast cancer, OPG interacted with glucose-regulated protein/binding immunoglobulin protein (GRP78/BiP), the endoplasmic reticulum (ER) chaperone and master regulator of the unfolded protein response, to promote cell apoptosis and prolong the survival of inflammatory breast cancer cells [ 47 ]. By forming complexes with the lipid raft core protein Cav-1 and EGFR, RANK promoted gastric cancer cell migration, and this effect was mitigated by OPG [ 48 ].…”
Section: Molecular Structure and Expression Of Opgmentioning
confidence: 99%
“…Pre-clinical studies have shown that carbon monoxide upregulates sestrin-2 through the PERK-eIF2α-ATF4 signaling pathway and alleviates dietary methionine/choline deficiency induced hepatic steatosis ( 23 ). Salubrinal is a selective inhibitor of eIF2α dephosphorylation, which maintains the phosphorylation state of eIF2α and protects cells from ER stress-induced apoptosis ( 24 ). By inhibiting the dephosphorylation of eIF2α in ER stress, Salubrinal reduces hepatic steatosis and fat deposition ( 25 ).…”
Section: The Unfolded Protein Responsementioning
confidence: 99%
“…ROS Detection. Following previous research [35], the level of reactive oxygen species (ROS) was analyzed using a DCFDA/H2DCFDA-Cellular ROS Assay (ab113851; Abcam, Cambridge, UK) according to the manufacturer's instruction.…”
Section: Enzyme-linked Immunosorbent Assay (Elisa)mentioning
confidence: 99%